Sensory attributes and acceptability of complementary foods fortified with Moringa oleifera leaf powder. Issue 3 (13th May 2019) - Boateng, Laurene; Nortey, Eunice; Ohemeng, Agartha N.; Asante, Matilda; Steiner-Asiedu, Matilda
Abstract : Purpose: Inadequacies in several micronutrients in complementary foods, notably iron, zinc, calcium, vitamin A, vitamin B6 and riboflavin have been reported. Moringa oleifera leaf powder (MLP), prepared from dried moringa leaves is nutrient-rich and has been explored for the treatment of micronutrient deficiencies among children in developing countries. This increasing interest in the use of moringa oleifera leaves to improve complementary foods notwithstanding, the unique sensory characteristics of the leaf powder potentially holds implications for the acceptability of local diets that are fortified with it. The purpose of this paper is to investigate the levels of MLP fortification that are most acceptable for feeding infants and young children. Design/methodology/approach: The authors performed a review of the literature, with the aim of investigating the sensory attributes and acceptable levels of fortification of complementary food blends fortified with different levels of MLP. Findings: The minimum amount of MLP to be added to a complementary food blend to observe significant improvements in its nutritional value was estimated to be about 10 per cent. However, at this 10 per cent fortification level also, sensory attributes of the products begin to become less desirable. Practical implications: For the success of nutrition interventions that involve the use of MLP to improve the nutritional quality of complementary foods, there is a need to consider the acceptability of the sensory attributes of the formulated blends in the target group. Safety of MLP as an ingredient in infant foods must also be investigated. Originality/value: The authors of this paper make recommendations for the use of MLP to fortify complementary foods to ensure its success as a food fortificant in nutrition interventions. The researchers are not aware of any published study that focuses on this subject.